Basic financial management - Martin, John D; Petty, J. W; Keown, Arthur J; Scott, David F (New Jersey (US) : Prentice-Hall, 1991)
Scope and environment of financial management.
Valuation and the management of long-term investments.
Financial structure and dividend policy decisions.
Financial analysis, planning, and control.
Working capital management.
Long-term financing.
Speciall topics in financial management.
Keywords: ADMINISTRACION FINANCIERA; FINANZAS; GESTION FINANCIERA; ORGANIZACION DE MERCADOS FIANCIEROS; ESTRUCTURA FINANCIERA; POLITICA DE DIVIDENDOS